Electrooxidation of 2-Chlorophenol and 2,4,6-Chlorophenol on Glassy Carbon Electrodes Modified with Graphite–Zeolite Mixtures - Ureta-Zanartu, M; Berrios-Guinez, C; Garrido-Ramirez, E; Fernandez-Vidal, F (Kluwer Academic Publishers, 2014)
This work reports the behavior of zeolite–graphite electrodes for the oxidation of 2,4,6-trichlorophenol (2,4,6-TCP) and 2-chlorophenol (2-CP) in a pH 3, 0.5 M Na2SO4 electrolyte using cyclic voltammetry, chronoamperometry, electrochemical impedance and galvanostatic electrolysis. Three zeolites with different hydrophobic/hydrophilic balance were used, in order to determine the possible effect of this parameter. On glassy carbon (GC) modified with 80–20 % graphite–zeolite mixtures the voltammetric peak charge of 2-CP oxidation was higher than that on GC modified with graphite alone, clearly showing a catalytic effect of the zeolites. ZSM-5 was the more active zeolite, probably due to its hydrophobic character, which should favor its interaction with the also hydrophobic 2-CP. In agreement with this, the charge-transfer resistance of GC modified with a graphite-ZSM-5 mixture was about half that of GC modified with graphite alone, and its double-layer capacity about 50 % higher, indicating a modification of the interface which favours the reaction. On the contrary, for 2,4,6-TCP both the oxidation peak charge, and the charge-transfer resistance, for GC electrodes modified with graphite–zeolite mixtures was about the same as that of GC modified with graphite alone. This lack of catalytic action could be due to the fact that the oxidation of 2,4,6-TCP requires the release of at least one chlorine atom, this release being so difficult that it cannot be promoted by any of the zeolites studied. However, in prolonged galvanostatic electrolysis practically all the current went to the oxidation of 2,4,6-TCP, while in the case of 2-CP only a small fraction was oxidized. Probably with 2-CP at long times surface poisoning blocked the reaction, as reflected by the fact that the electrolysis potential rose to a value 0.2 V higher than that reached by TCP, and so high that most of the current went to oxygen evolution. The zeolites ZA and ZY decreased the mineralization of 2,4,6-TCP, since they promoted a one-electron oxidation reaction, so that its concentration at 80 min was about 80 % of that observed with graphite alone. The oxidation of 2-CP was not significantly affected by any zeolite as compared with that on graphite. © 2014, Springer Science+Business Media Dordrecht.